Coccidiose em frangos de corte: revisão bibliográfica - Araujo, Matheus Aparecido Niedo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Maintaining the health of animals in captivity is essential to obtain good levels of productivity and profitability. At aviaries the health is extremely important considering that adult chicks and chickens can be affected with diseases and problems with the environment when it is not well managed. Diseases such as avian coccidiosis cause countless losses to the agricultural sector, which makes the producer face numerous problems if he does not perform good care in the care of the chickens. The aim of this study was to carry out a bibliographic survey, in order to better understand the aspects related to coccidiosis, such as the characteristics of protozoa, the pathogenesis and possible methods of prevention, control and how the diagnosis is made in broiler chickens. It was possible to verify that the species E. acervulina, E. maxima, and E. tenella are the most economically important due to their geographical dissemination capacity and the severity of symptoms when infection occurs in broiler poultry houses. Control can be carried out with measures that can help prevent outbreaks of this disease, such as cleaning the sheds, strictly following a sanitary control program, following an appropriate medication protocol, in addition to adopting the proper management of the aviary. After a brief analysis of works related to coccidiosis in broilers, it is necessary to understand that this disease is very demanding in terms of attention and care, as it causes a high economic loss for poultry producers. Despite technification and advances in science regarding research, treatments and medicines to improve the life of chickens, the management of coccidiosis requires a serious commitment to ensure a reduction in its incidence, it is enough to comply with sanitary requirements in a good anticoccidial planning.

Manter a sanidade dos animais em cativeiros é imprescindível para se obter bons níveis de produtividade e rentabilidade. Em aviários a sanidade é de extrema importância tendo em vista que pintos e frangos adultos podem ser acometidos com doenças e problemas com o ambiente quando não são bem manejados. Doenças, como a coccidiose aviária, causam inúmeros prejuízos para o setor agropecuário, o que faz com que o produtor enfrente inúmeros problemas caso não execute bons tratos no cuidado dos frangos. O objetivo do presente trabalho foi realizar um levantamento bibliográfico, com o intuito de conhecer melhor os aspectos relacionados à coccidiose, como as características dos protozoários, a patogenia e possíveis métodos de prevenção, controle e como é realizado o diagnóstico em frangos de corte. Foi possível constatar que as espécies E. acervulina, E. maxima, e E. tenella, são as de maior importância econômica devido a sua capacidade de disseminação geográfica e a severidade dos sintomas quando ocorre infecção nos aviários de frango de corte. O controle pode ser realizado com medidas que podem contribuir para evitar surtos dessa doença, como a limpeza dos galpões, seguir rigorosamente um programa de controle sanitário, obedecendo a um protocolo de medicação apropriado, além de adoção do manejo adequado ao aviário. Após a sucinta análise de trabalhos relacionados à coccidiose em frangos, é preciso compreender que esta doença é muito exigente em atenção e cuidados, pois causa elevado prejuízo econômico para os produtores de carne de frango. Apesar da tecnificação e dos avanços da ciência em relação às pesquisas, tratos e medicamentos para melhorar a vida dos frangos, o manejo da coccidiose exige sério comprometimento para garantir a diminuição de sua incidência, basta cumprir as exigências sanitárias em um bom planejamento anticoccidiano.
Coccidiosis in broiler chickens: bibliographic review
Keywords: Gallus gallus domesticus; Pathogenesis; Gallus domesticus; Eimeria spp.; Patogenia